Impact of home monitoring program on interstage mortality after the Norwood procedure - Staehler, Helena; Schaeffer, Thibault; Wasner, Johanna; Lemmer, Julia; Adam, Michel; Burri, Melchior; Hager, Alfred; Ewert, Peter; Hörer, Jürgen; Ono, Masamichi; Heinisch, Paul Philipp (Frontiers in Cardiovascular Medicine, 2023)
Objective: While early outcome after the Norwood operation for hypoplastic left heart syndrome has improved, interstage mortality until bidirectional cavopulmonary shunt (BCPS) remains a concern. Our aim was to institute a home monitoring program to (HMP) decrease interstage mortality. Methods: Among 264 patients who survived Norwood procedure and were discharged before BCPS, 80 patients were included in the HMP and compared to the remaining 184 patients regarding inter-stage mortality. In patients with HMP, events during the interstage period were evaluated. Results: Interstage mortality was 8% (n=21), and was significantly lower in patients with HMP (2.5%, n=2), compared to those without (10.3%, n=19, p = 0.031). Patients with inter-stage mortality had significantly lower birth weight (p<0.001) compared to those without. Lower birth weight (p<0.001), extra corporeal membrane oxygenation support (p=0.002), and lack of HMP (p=0.048) were risk factors for inter-stage mortality. Most frequent event during home monitoring was low saturation (<70%) in 14 patients (18%), followed by infection in 6 (7.5%), stagnated weight gain in 5 (6.3%), hypoxic shock in 3 (3.8%) and arrhythmias in 2 (2.5%). An unexpected readmission was needed in 24 patients (30%). In those patients, age (p=0.001) and weight at BCPS (p=0.007) were significantly lower compared to those without re-admission, but the survival after BCPS was comparable between the groups. Conclusions: Interstage HMP permits timely intervention and led to an important decrease in inter-stage mortality. One-third of the patients with home monitoring program needed re-submission and demonstrated the need for earlier stage 2 palliation.